Literary Politics
XII, 207 p.
Keywords: Literary Politics identifies and debates competing definitions of 'English Studies' as an academic subject, celebrates the diversity of contemporary literary studies, and demonstrates the ways in which a range of literary texts can be understood as politically engaged, sometimes in unexpected ways.